Connotative aspect of verbal nomination in modern German language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article discusses the concept of «connotation», the nature and components of connotative meanings of the word. Analyzes the characteristics and dynamics of connotative process in lexical-semantic groups of verbs German.
Keywords: connotation; connotative meaning; denotative meaning; emotional; evaluative; expressive component; verb